Maximum torque per ampere and maximum power per ampere sliding mode control for interior permanent magnet synchronous motors - Hashim Alnami; Chengzong Pang; Avinash Papineni; Xin Wang (Systems Science & Control Engineering, 2021)
This paper presents novel maximum torque per ampere (MTPA) and maximum power per ampere (MPPA) sliding mode control (SMC) approaches for interior permanent-magnet synchronous motors (IPMs). We first derive the first-order SMC methods to improve the field-oriented control's resiliency against the external perturbations, extraneous noise and modelling uncertainties. After that, we propose the higher-order SMC to significantly reduce the chattering phenomenon, which is inherent in the first-order sliding mode method. Based on the comparison studies, the conventional proportional-integral-derivative based field oriented control shows sluggish response and is more sensitive to parameter perturbations and external torque disturbances. By introducing the novel SMC methods, both the speed and torque regulation performance of interior permanent magnet synchronous motor can be greatly improved. Computer simulation studies have demonstrated the superior performance of the first-order and higher-order sliding mode controllers for interior permanent magnet synchronous motor speed and torque regulation applications.